Sistem Informasi Bimbingan Skripsi Berbasis Website Pada Pendidikan Agama Hindu Institut Agama Hindu Negeri Tampung Penyang - Arya, I Made; Christina, Sherly; Parhusip, Jadiaman (Universitas Palangka Raya, 2023)
Thesis is a scientific paper that discusses a problem in a particular field of science by using applicable scientific rules. Apart from being a graduation requirement.. However, there are several obstacles in the preparation of the thesis, one of which is thesis guidance. It is necessary to have a system to minimize obstacles during thesis consultation. The Website Thesis Consultation Information System in this study uses the Waterfall software development method. The stages used are communication, planning, modeling, construction, and deployment. System analysis was made using flowcharts and system design using Unified Modeling Language (UML). And the testing method used in this research is black box testing. Results using the blackbox testing method from the analysis and operation process, it is found that this system can help students, lecturers and study programs in the thesis consultation process.